The effect of consumption of Scylla Serrata on haematological parameters in rats / Nur Syahiirah Saberi - Saberi, Nur Syahiirah (2015)
Mud crab (Scylla serrata) is a source that is believed can treat certain blood disorders. Currently, the scientific knowledge about mud crab is still lacking in Malaysia. The aimed of this study is to determine the effect of mud crab on haematological parameters in rats. Aqueous extract of mud crab was prepared from cooked samples and then was freeze dried to powdered form. Its protein content was estimated by using Bradford assay. Eighteen male Wistar rats were randomly divided into three groups (two treatment groups and control group) of six rats (n=6). All groups were kept under similar condition. Mud crab stock solutions were prepared in 7.0 mg/ml protein/kg and 52 mg/ml protein/kg doses and orally administered to treatment groups for three weeks. Distilled water was used to control group. Blood samples were obtained from each rat via cardiac puncture for further analysis of various haematological parameters. The result revealed that the average protein content of the extract was 5.2 ±0.06 mg/ml protein/kg. RBC, Hb, HCT and MCH level increased significantly in the treatment groups compared to control group. In conclusion, mud crab contains vital nutrients that boost production of red blood cell indices, hence could serve as an essential food supplement to treat anemia.